Junior High School Teachers' Perception of Blended Learning in English Language Teaching in Yogyakarta - Widig Cahyono; Ari Purnawan; Anas Sumarhadi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This study aims to analyze the perception of junior high school English teachers towards the implementation of blended learning in Yogyakarta and to determine the frequency of its implementation. Data were collected through questionnaires from 84 junior high school English teachers using purposive sampling techniques. The research instrument uses a 5-point Likert scale to measure seven dimensions: knowledge and understanding, ICT competence, frequency of implementation, perceived effectiveness, perceived benefits, perceived challenges, and institutional support. Data analysis employed descriptive statistics and non-parametric tests. The results showed that teachers' perceptions of blended learning were positive overall, with the highest score on the perceived effectiveness dimension (M = 16.50; SD = 2.42). However, the frequency of implementation remains low (M = 10.61; SD = 2.14). Analysis based on demographic variables showed that only training experience had a significant effect on teacher perception (p = 0.006). There is a gap between positive perception and practical implementation, highlighting the need for infrastructure support, intensive training, and policies to support the implementation of blended learning in English language teaching.